Pengaruh Motivasi Kerja dan Stres Kerja Terhadap Kinerja Karyawan di PT. Astra Credit Companies Cab. Kwitang - Raihan Fajri; Nurvi Oktiani (Institut Nalanda, 2024)
The purpose of this research is to determine the variable influence of work motivation and work stress on the performance of employees of PT. Astra Credit Compaines Kwitang Branch. The research used is a quantitative method. The research took a sample of 32 employees at PT. Astra Credit Compaines Kwitang Branch, then the results showed motivation variables work and work stress have a significant influence on employee performance. Work motivation and work stress are important variable components in improving employee performance